Solving Fourth Order Differential Non-Linear Equations, Existence and Uniqueness - Malbanji, Amer Mahmoud (2017)
A Master of Science thesis in Mathematics by Amer Mahmoud Malbanji entitled, "Solving Fourth Order Differential Non-Linear Equations, Existence and Uniqueness," submitted in May 2017. Thesis advisor is Dr. Suheil A. Khoury. Soft and hard copy available.